Spatial-temporal variability of carbon emission and sequestration and coupling coordination degree in Beijing district territory - Mengjie Song; Ye Zhao; Jia Liang; Fangfang Li (Cleaner Environmental Systems, 2023)
Estimating the variation of carbon emissions and vegetation carbon sequestration, and understanding the coupling coordination relationships between carbon emissions and the eco-environment are essential for promoting sustainable development. To analyze the distribution of carbon emissions, a calculation model for carbon emissions was proposed through integrating nighttime light datasets and land use data. The results showed that the model proposed was appropriate and reliable for carbon emissions on land of different utilization types. The distribution of vegetation carbon sequestration was estimated by the CASA model. The combined results showed that carbon emissions have been greater than vegetation carbon sinks in Beijing from 2003 to 2019, with the difference reaching a maximum in 2007 and showing an overall trend of first increasing and then decreasing from 2003 to 2019. The northern and southwestern area in Beijing had a stronger carbon sink capacity, and carbon emissions were mainly concentrated in the southwest region of Beijing. Additionally, we analyzed the coupling coordination degree (CCD) between carbon emissions (CE) and the eco-environment (EE). The CCD showed a fluctuating upward trend in Beijing from 2003 to 2019, and 16 districts were all out of a moderate-decoupled state in 2015. This study will enrich the body of carbon emission and vegetation NPP research at the district level and will provide scientific support to the achievement of “Dual Carbon” targets in Beijing and other Chinese cities.